From Physical Assets to Digital Assets: Reconstructing Firm Value in Modern Accounting Perspective - Arief Fahruri (Dhana, 2026)
The rapid advancement of digital technologies has fundamentally altered the composition of firm value, shifting the locus of value creation from tangible, physical assets to intangible, digital assets. Traditional accounting frameworks, rooted in historical cost conventions and physical asset recognition, increasingly fail to capture the full economic value of digitally-intensive firms. This conceptual study examines the theoretical and empirical implications of this shift, drawing on Resource-Based Theory, Digital Platform Theory, and Stakeholder Value frameworks. Using a systematic literature review approach, we synthesize evidence from 20 peer-reviewed studies published in leading international journals. Our findings indicate that digital assets, including artificial intelligence capabilities, data ecosystems, blockchain infrastructure, and metaverse platforms, now constitute the primary drivers of firm value in the modern economy. We identify critical gaps in current International Financial Reporting Standards (IFRS) and Generally Accepted Accounting Principles (GAAP) in recognizing and measuring digital assets. The paper proposes a conceptual Digital Asset Value (DAV) framework that integrates technological capability, network effects, scalability, and cybersecurity resilience as core dimensions of modern firm valuation. This research contributes to accounting theory by extending the boundaries of asset recognition and to practice by guiding standard-setters and firms in rethinking value measurement in the digital economy.